Optimasi Komposisi Lactobacillus bulgaricus dan Streptococcus thermophilus pada Yogurt Terfortifikasi Buah Lakum (Cayratia trifolia (L.) Domin) sebagai Antibakteri terhadap Escherichia coli - Rahman, Ika Ristia; Nurkhasanah,; Kumalasari, Ika (Pharmaceutical Sciences and Research, 2019)
Optimization of composition of Lactobacillus bulgaricus and Streptococcus thermophilus in yoghurt fortified by lakum fruit (Cayratia trifolia (L.) Domin) extract as an antibacterial against Escherichia coli was investigated for the first time in this research. Yoghurt was made by fermenting milk with several compositions of L. bulgaricus and S. thermophilus as starter cultures and also adding lakum fruit extract as an antibacterial against E. coli. The fermentation process was depended on the bacterial culture used. The aim of the research was to determine the optimal composition of L. Bulgaricus and S. thermophilus bacteria in lakum fruit yoghurt as an antibacterial against E. coli. The research was done by making variation of composition of L. bulgaricus and S. thermophilus bacteria culture in lakum fruit yoghurt. Lakum fruit yoghurt was analysed with acidity stability test, pH, anthocyanin level and inhibitory activity against E. coli. The data analysis was done with MANOVA (Multivariate Analysis of Variance). The results showed that lakum fruit yoghurt with composition of L. bulgaricus and S. thermophilus 2:1 (v/v) had a good stability with increased acidity dan decreased pH. The value of anthocyanin in lakum fruit yogurt decreased and plain yoghurt (without lakum fruit extract) with composition of L. bulgaricus and S. thermophilus 2:1 (v/v) gave the highest inhibitory value against E. coli.